Squamate reptiles may have compensated for the lack of γδTCR with a duplication of the TRB locus - Jordan M. Sampson; Kimberly A. Morrissey; Kieran J. Mikolajova; Kourtney M. Zimmerly; Neil J. Gemmell; Michael G. Gardner; Terry Bertozzi; Terry Bertozzi; Robert D. Miller (Frontiers in Immunology)
Squamate reptiles are amongst the most successful terrestrial vertebrate lineages, with over 10,000 species across a broad range of ecosystems. Despite their success, squamates are also amongst the least studied lineages immunologically. Recently, a universal lack of γδ T cells in squamates due to deletions of the genes encoding the T cell receptor (TCR) γ and δ chains was discovered. Here, we begin to address how the loss of γδ T cells may have impacted the evolution of the squamate immune system. Using the skink Tiliqua rugosa, we found that squamates have not significantly increased the complexity of conventional T cell receptor beta (TCRβ or TRB) chain V regions compared to that of the nearest living squamate relative, the tuatara, Sphenodon punctatus or other amniotes. Our analyses include a putative new TCR locus. This novel locus contains V, D, and J gene segments that undergo V(D)J recombination, albeit with a limited number of gene segments in most squamate species. Based on conserved residues, the predicted protein chain would be expected to form a heterodimer with TCRα. This new TCR locus appears to be derived from an ancient duplication of the TRB locus and is homologous to the recently described T cell receptor epsilon (TRE). TRE is absent from the genomes of the tuatara and all Archosaurs examined and appears squamate specific.